TRENDS IN ROMANIA'S TRADE WITH WALNUTS IN THE PERIOD 2010-2022 - Georgiana Armenița ARGHIROIU; Silviu BECIU; Maria BOBEICĂ (COLPOȘ) (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to follow the recent developments regarding the production and Romanian trade with fresh or dried walnuts in shell or shelled. Both statistical and specific indicators of international trade are used. The results indicated that Romania increased its production of walnuts and performed well in trade with shelled walnuts, and the trade balance was positive in the entire analysed period. Is not the case of the trade with walnuts in shell, where the trade balance was consistently negative. Most part of the Romanian trade with walnuts is either with EU countries or with the neighbour countries which are not EU members.